The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1995
DOI: 10.1159/000172329
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Pilonidal Sinus: Etiology and Treatment

Abstract: A clinical and histologic study of recurrent pilonidal sinus is presented. During a 5-year period 44 patients were treated for recurrent pilonidal sinus. Of these, recurrence had occurred within 1 year in 26 patients (76%). After 26 reoperations with excision and primary suture further recurrence was seen in 23% (6/26), and in 24% (6/25) after reoperations with open treatment. The histologic findings in recurrent sinuses (18 patients) were almost identical to that of primary disease. Recurrent sinuses were sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…These results agree with Youssef et al (33) as hyposthesia was recorded in (10%) of Limberg group and (3.3 %) in the primary repair group. This also comparable with the studies conducted by Akin et al (34) and Søndenaa et al (35) who reported hyposthesia in (8.9%) and (9.5%) of their patients, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…These results agree with Youssef et al (33) as hyposthesia was recorded in (10%) of Limberg group and (3.3 %) in the primary repair group. This also comparable with the studies conducted by Akin et al (34) and Søndenaa et al (35) who reported hyposthesia in (8.9%) and (9.5%) of their patients, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Data on recurrence and follow-up times in primary open PSD treatment pertaining to 21,583 patients were extracted from 205 additional non-RCTs 4 , 60 , 74 , 75 , 111 , 112 , 114 , 115 , 117 , 118 , 121 – 126 , 128 – 134 , 136 , 137 , 141 , 143 , 149 , 153 – 156 , 160 , 161 , 163 , 167 – 171 , 174 , 175 , 177 , 181 , 182 , 188 192 , 194 , 196 , 197 , 199 – 201 , 203 , 206 , 208 , 215 , 216 , 218 , 220 , 221 , 223 , 224 , 230 , 233 , 237 – 373 . Among these patients, a recurrence of 3.4% (95% CI 3.1–3.6%) was observed in patients at 12 months, 7.0% (95% CI 6.5–7.4%) at 24 months, 16.8% (95% CI 15.8–17.8%) at 60 months, 32.0% (95% CI 29.6–34.4%) at 120 months, and 67.9% (95% CI 53.3–82.4%) at 240 months (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the variables associated with recurrence of PNS are believed to be related to the "patient" such as obesity, hirsute nature, smoking, positive family history, and age at first surgery. Other factors are related to the "primary procedure", such as type of surgery, post-operative wound complications (mainly infection) and the timing of recurrence postoperatively [35]. All such variables were similar between the two groups under comparison, and so were the "sinus characteristics" that included the chief symptom, duration of symptoms, as well as location and number of sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we compared also the results of Karydakis technique versus midline closure in patients with "primary" and "recurrent" PNS separately, and demonstrated that complication and recurrence rates were significantly less with the Karydakis flap in both subgroups. Over a 5-year period, Sondenaa et al [35], treated 44 patients with recurrent PNS using excision and primary midline closure. They reported a high re-recurrence rate of 59.1% (26/44) during the first year post-operatively and attributed this high incidence, at least in part, to the high rate of post-operative infection.…”
Section: Discussionmentioning
confidence: 99%